Black feminist thought: Knowledge, consciousness, and the politics of empowerment - Hill Collins, Patricia (Routledge, 2000)
A revision of a hugely successful book; this is the 'bible' of contemporary black feminist thought and is widely cited and taught as a seminal text. Completely up-to-date with recent events, trends in popular culture, current events, and politics.
Keywords: 1900-1999; EDI; afro-féminisme; amériques; approches et analyses; discipline; féminismes noirs; incontournable; intersectionnalité; justice sociale; militance; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppression; thématiques; épistémologie; états-unis